Task-Dependent Masked Priming Effects in Visual Word Recognition - Kinoshita, Sachiko; Norris, Dennis (Frontiers in Psychology, 2012)
A method used widely to study the first 250 ms of visual word recognition is masked priming: These studies have yielded a rich set of data concerning the processes involved in recognizing letters and words. In these studies, there is an implicit assumption that the early processes in word recognition tapped by masked priming are automatic, and masked priming effects should therefore be invariant across tasks. Contrary to this assumption, masked priming effects are modulated by the task goal: For example, only word targets show priming in the lexical decision task, but both words and nonwords do in the same-different task; semantic priming effects are generally weak in the lexical decision task but are robust in the semantic categorization task. We explain how such task dependence arises within the Bayesian Reader account of masked priming (Norris & Kinoshita, 2008), and how the task dissociations can be used to understand the early processes in lexical access.